Total Phenol Content and Antioxidant Activity of Different Celta Pig Carcass Locations as Affected by the Finishing Diet (Chestnuts or Commercial Feed) - Noemí Echegaray; Paulo E. S. Munekata; Juan A. Centeno; Rubén Domínguez; Mirian Pateiro; Javier Carballo; José M. Lorenzo (MDPI AG, 2020)
The objective of this research was to evaluate the total phenol content, total flavonoids, and antioxidant activity of chestnuts (Castanea sativa Mill.) and commercial feed employed in the finishing diet of the Celta pig breed and analyze the effect of the feeding (chestnuts vs. commercial feed) in the finishing diet on total phenol content and antioxidant activity of Longissimus thoracis et lumborum, Psoas major, and Biceps femoris muscles and liver of the Celta pig breed. The antioxidant activity of the feed and animal tissue was investigated using three antioxidant methods (2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, 2-2'-Azino-di-[3-ethylbenzthiazoline sulfonate] (ABTS) radical scavenging activity, and ferric reducing antioxidant power (FRAP) assay). The determination of the total phenol content and total flavonoids showed that chestnut had a significantly lower concentration than commercial feed in these compounds (130.00 vs. 312.89 mg gallic acid equivalents/100 g fresh weight and 8.58 vs. 32.18 mg catechin equivalents/100 g fresh weight, respectively). However, the results displayed that chestnuts had a higher antioxidant activity when compared with the commercial feed through the DPPH and ABTS methods (1152.42 vs. 957.33 µg Trolox equivalents/g fresh weight, and 9379.74 vs. 7613.44 µg Trolox equivalents/g fresh weight, for DPPH and ABTS assay, respectively), while the antioxidant activity measured by the FRAP assay turned out to show higher values for commercial feed (1777.49 and 1946.09 µmol Fe2+/100 fresh weight for chestnut and commercial feed, respectively), although significant differences were only found in the ABTS assay. On the other hand, the present study found that chestnut significantly reduces the total phenol content and declines the antioxidant activity of Longissimus thoracis et lumborum, Psoas major, and Biceps femoris muscles and liver of the Celta pig breed. Finally, it has been found that liver is the location that has the best antioxidant characteristics compared to any muscle, regardless of diet utilized.